2016
DOI: 10.1186/s40064-016-3446-0
|View full text |Cite
|
Sign up to set email alerts
|

Intuitionistic fuzzy-based model for failure detection

Abstract: In identifying to-be-improved product component(s), the customer/user requirements which are mainly considered, and achieved through customer surveys using the quality function deployment (QFD) tool, often fail to guarantee or cover aspects of the product reliability. Even when they do, there are always many misunderstandings. To improve the product reliability and quality during product redesigning phase and to create that novel product(s) for the customers, the failure information of the existing product, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…We use Buckley's Fuzzy-AHP to find importance weights since it is simple to cover to the fuzzy case and assurances a sole solution to the reciprocal comparison matrix [28]. It is rather easier than the other Fuzzy-AHP approaches.…”
Section: Fuzzy Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…We use Buckley's Fuzzy-AHP to find importance weights since it is simple to cover to the fuzzy case and assurances a sole solution to the reciprocal comparison matrix [28]. It is rather easier than the other Fuzzy-AHP approaches.…”
Section: Fuzzy Setsmentioning
confidence: 99%
“…This threshold value ( NI ) is calculated with the following formula. (28) Dominance relations among alternatives is obtained to unit elements in matrix.…”
Section: Elements Klmentioning
confidence: 99%
“…A key requirement of reliability management in wind turbines is the task of a prior detection of failures. This is necessary to ensure reliable continuous operation and maintenance of wind turbine machine systems (Kusiak & Li, 2011;Aikhuele & Turan, 2016, 2018. A priori failure detection in wind turbine is a prerequisite for ensuring failure prediction maintenance (Nivedh, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive review of the IFS, which is represented by IFN for solving MCDM problems, has shown an increase over the past few years as revealed in the literature [8][9][10][11][12][13][14][15][16][17][18] with a few extensions of the IFN, such as the trapezoidal IFN (TrIFN) [19,20], the interval-valued TrIFN (IVTrIFN) [21,22], Pythagorean IFN (PIFN) [23] and the triangular IFN (TIFN) [24][25][26]. This study, however, will be concerned with the triangular intuitionistic fuzzy numbers (TIFNs) only, with the purpose of accounting for the attitudinal character or risk attitude of the DMs, which have not been fully studied in the reviewed literature.…”
Section: Introductionmentioning
confidence: 99%